Ultrasound measurement of the size of the anterior tibial muscle group: the effect of exercise and leg dominance - McCreesh Karen; Egan Sinead (BMC, 2011)
Abstract Background Knowledge of normal muscle characteristics is crucial in planning rehabilitation programmes for injured athletes. There is a high incidence of ankle and anterior tibial symptoms in football players, however little is known about the effect of limb dominance on the anterior tibial muscle group (ATMG). The purpose of this study was to assess the effect of limb dominance and sports-specific activity on ATMG thickness in Gaelic footballers and non-football playing controls using ultrasound measurements, and to compare results from transverse and longitudinal scans. Methods Bilateral ultrasound scans were taken to assess the ATMG size in 10 Gaelic footballers and 10 sedentary controls (age range 18-25 yrs), using a previously published protocol. Both transverse and longitudinal images were taken. Muscle thickness measurements were carried out blind to group and side of dominance, using the Image-J programme. Results Muscle thickness on the dominant leg was significantly greater than the non-dominant leg in the footballers with a mean difference of 7.3%, while there was no significant dominance effect in the controls (p < 0.05). There was no significant difference between the measurements from transverse or longitudinal scans. Conclusions A significant dominance effect exists in ATMG size in this group of Gaelic footballers, likely attributable to the kicking action involved in the sport. This should be taken into account when rehabilitating footballers with anterior tibial pathology. Ultrasound is a reliable tool to measure ATMG thickness, and measurement may be taken in transverse or longitudinal section.